Gender differences in eating behavior and environmental attitudes: the mediating role of the Dark Triad - Mertens, Alica; Krause, Mischa von; Denk, Alexandra; Heitz, Theresia (Personality and individual differences, 2021)
Recently, Machiavellianism was identified as potential mediator explaining gender differences in meat-eating justification strategies, which in turn predicted meat consumption. The current study aimed to - on the one hand - replicate this empirical finding and to - on the other hand - investigate the mediating role of the Dark Triad with regard to gender differences in pro-environmental attitudes. Five-hundred-forty-eight participants took part in the study. Women compared to men justified meat-eating less and held more positive attitudes toward the environment. More importantly, we replicated the finding that the association between gender and meat-eating justification strategies is mediated by Machiavellianism. Additionally, the association between gender and pro-environmental attitudes was mediated by psychopathy. These findings support the idea that while Machiavellianism is an important mediator explaining gender differences in meat-eating justification strategies, psychopathy is able to explain gender differences in attitudes toward the environment.